The Association of New-Onset Acute Kidney Injury and Mortality in Critically Ill Patients With COVID-19 With Less Severe Clinical Conditions at Admission: A Moderation Analysis - Regolisti, Giuseppe; Maggiore, Umberto; Di Mario, Francesca; Gentile, Micaela; Benigno, Giuseppe Daniele; Gandolfini, Ilaria; Pistolesi, Valentina; Morabito, Santo; Barbagallo, Maria; Picetti, Edoardo; Fiaccadori, Enrico (Frontiers in Medicine, 2022)
Acute kidney injury (AKI), electrolyte and acid-base disorders complicate the clinical course of critically ill patients with coronavirus-associated disease (COVID-19), and are associated with poor outcomes. It is not known whether the severity of clinical conditions at admission in the intensive care unit (ICU) changes the clinical significance of AKI and/or electrolyte or acid-base disorders developing during ICU stay. We conducted a retrospective study in critically ill patients with COVID-19 to evaluate whether the severity of clinical conditions at admission in the ICU affects the impact of AKI and of serum electrolytes or acid-base status on mortality. We carried out a 28-day retrospective follow-up study on 115 critically ill patients consecutively admitted to ICU for severe COVID-19 at a tertiary care university hospital and surviving longer than 24 hours. We collected baseline demographic and clinical characteristics, and longitudinal data on kidney function, kidney replacement therapy, serum electrolytes and acid-base status. We used Cox proportional hazards multiple regression models to test the interaction between the time-varying variates new-onset AKI or electrolyte or acid-base disorders and Sequential Organ Failure Assessment (SOFA) score at admission. After adjusting for age, sex, Charlson’s comorbidity index and AKI present at ICU admission, new-onset AKI was significantly associated with 28-day mortality only in the patients in the lower and middle SOFA score tertiles (lowest SOFA tertile, hazard ratio 4.27 [95 percent confidence interval: 1.27 to 14.44; P= 0.019], middle SOFA tertile, hazard ratio 3.17 [95 percent confidence interval: 1.11 to 9.04, P= 0.031], highest SOFA tertile, hazard ratio 0.77 [95 percent confidence interval: 0.24 to 2.50; P=0.66]; P= 0.026 for interaction with SOFA as a continuous variable). SOFA at admission did not affect the relationship of serum electrolytes and acid-base status with mortality, except for new-onset acidosis which was associated with increased mortality, with the hazard ratio of death increasing with SOFA score (P<0.001). Thus, unlike in the most severe critically ill patients admitted to the intensive care unit for COVID-19, in patients with less severe condition at admission the development of AKI during stay is a strong indicator of increased hazard of death.